2007
DOI: 10.1681/asn.2006091067
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Transient Receptor Potential 1 Channel Is Involved in Contractile Function of Glomerular Mesangial Cells

Abstract: Contractility of mesangial cells (MC) is tightly controlled by [G lomerular mesangial cells (MC) are located within glomerular capillary loops and contribute to the physiologic regulation of glomerular hemodynamics (1). Altered responsiveness of MC to hormones is one of the major causes that lead to various renal diseases. Ca 2ϩ influx across the plasma membrane is a major component of MC responses to vasoconstrictors (1). Several types of Ca 2ϩ -conductive channels in the plasma membrane are involved in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 38 publications
5
57
0
Order By: Relevance
“…Recently, Niehof and Borlak (32) reported that HNF4␣ protein was significantly reduced in kidneys from diabetic rats and humans. The decrease in HNF4␣ in the diabetic kidney downregulated expression of TRPC1 protein, a Ca 2ϩ channel that regulates Ca 2ϩ signals in kidney cells (10). In the present study, we provide evidence that HNF4␣ can regulate another type of Ca 2ϩ channel, i.e., SOCs, by repressing STIM1 transcription.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Recently, Niehof and Borlak (32) reported that HNF4␣ protein was significantly reduced in kidneys from diabetic rats and humans. The decrease in HNF4␣ in the diabetic kidney downregulated expression of TRPC1 protein, a Ca 2ϩ channel that regulates Ca 2ϩ signals in kidney cells (10). In the present study, we provide evidence that HNF4␣ can regulate another type of Ca 2ϩ channel, i.e., SOCs, by repressing STIM1 transcription.…”
Section: Discussionsupporting
confidence: 57%
“…A recent study by Niehof and Borlak (32) showed that HNF4␣ protein expression was repressed in kidneys of both diabetic rats and humans and that the reduced HNF4␣ might contribute to diabetic nephropathy by inhibiting canonical transient receptor potential (TRP)C1 protein in the kidney (32). Since TRPC1 is a Ca 2ϩ -permeable channel expressed in kidney cells (10), the results of Niehof and Borlak's study suggest that HNF4␣ may affect diabetic renal changes by regulating renal cell Ca 2ϩ signaling. STIM1-gated Ca 2ϩ channels participate in the Ca 2ϩ response in glomerular MCs (39,42), and dysfunction of MCs contributes to the progression of diabetic kidney disease.…”
mentioning
confidence: 99%
“…We propose TRPC1 to be a disease candidate gene in diabetic nephropathy. Recently, TRPC1 was identified in glomerular mesangial cells (29,30) to contribute to contractile function (31). Essentially, mesangial cells are located within glomerular capillary loops and play a role in the physiological regulation of glomerular hemodynamics and filtration (28,30).…”
Section: Discussionmentioning
confidence: 99%
“…Since human MCs possess multiple isoforms of TRPC channel proteins (36), we inferred that the resting tone of MCs might be the function of those TRPC isoforms or could be mediated by other types of ion channels in the plasma membrane. Indeed, we recently found that the biological knockdown of TRPC1 using an RNAi approach or functional blockade of TRPC1 channel using a specific TRPC1 antibody significantly reduced basal membrane currents in cultured MCs (8).…”
Section: Discussionmentioning
confidence: 99%